A prospective randomised study of a rotary powered device (OnControl) for bone marrow aspiration and biopsy. Issue 9 (23rd May 2011) - Swords, Ronan T; Anguita, Javier; Higgins, Russell A; Yunes, Andrea C; Naski, Michael; Padmanabhan, Swaminathan; Kelly, Kevin R; Mahalingam, Devalingam; Philbeck, Thomas; Miller, Larry; Puga, Tatiana A; Giles, Francis J; et al.
Abstract : Introduction: Bone marrow aspiration and biopsy is an invasive procedure associated with morbidity and mortality risk. We compared a powered bone marrow aspiration and biopsy device to the traditional method by relatively assessing pain scores, procedure times, biopsy capture rates, quality of material retrieved, and safety and operator satisfaction. Methods: Two large academic medical centres participated in this trial. Patients were randomised to have procedures carried out using the powered system or the manual technique. A visual analogue scale pain score was recorded immediately following skin puncture and once again at the end of the procedure for each patient. Procedure time was measured from skin puncture to core specimen acquisition. Pathologic assessment of 30 randomised samples was carried out. Operator satisfaction with devices was measured on a scale of 0–10, with 10 as the highest rating. Results: Five operators from two sites enrolled 50 patients (powered, n=25; manual, n=25). Groups were evenly matched, with no significant differences in the means for age, weight and height. The powered system was superior to the manual system with respect to patient perceived pain from needle insertion (2.6±2.0 vs 4.1±2.5, p=0.022) and procedural time (100.0±72.8 s vs 224.1±79.0 s, p<0.001). Overall pain scores at the end of both procedures were comparable (3.2±2.2 vs 3.8±3.0, p=0.438). No complications were observed in either arm of the study. Blinded pathologic analysis of the specimens retrieved revealed that cores obtained using the powered system were longer and wider than those obtained using the manual technique (25.4±12.3 mm 2 vs 11.9±5.6 mm 2, p=0.001). For marrow aspiration, no difference was seen between groups for clot/particle spicules or smear spicules. Operator assessment favoured the use of the powered device. Conclusions: Results of this trial suggest that the use of a powered bone marrow biopsy device significantly reduces needle insertion pain and procedural time when compared to a manual technique. The superior size and overall quality of core specimens retrieved by the powered device provides more material for pathologic evaluation, thereby increasing diagnostic yield and reducing the need for repeat procedures.